Promising health perspectives for human cloning - Rolando Schramm, Fermin (Acta Bioethica, 2003)
To evaluate the promises of human cloning, both therapeutic and reproductive, we can start from two pertinent points of view: health and secular bioethics. Under the point of view of health, though public prevention and health promotion policies, adequate to objective existing conditions, they try to protect human population from unnecessary diseases. Secular bioethics seeks to understand the ethics of cloning through rational analysis, free from the moral implications of its use; and if the conclusion is that it is legitimate, to propose it like a tool to protect human health. In spite of their apparently very different functions, both therapeutic cloning and reproductive cloning seek to respond to the challenge of unnecessary human suffering: therapeutic cloning, thanks to the technique that uses totipotent stem cells, seek to grow organs and tissues to eliminate avoidable suffering; reproductive cloning may also diminish forms of unnecessary human suffering and if can, therefore, to be considered a particular case of therapeutic approach.